Effect of supplementing compost with grapeseed meal on Agaricus bisporus production - Pardo-Gimenez, Arturo; Zied, Diego C. [UNESP]; Alvarez-Orti, Manuel; Rubio, Manuela; Pardo, Jose E. (Wiley-Blackwell, 2012)
BACKGROUND: This work assesses the agronomic performance of grapeseed meal, before and after oil extraction, in nutritional compost supplement when growing the mushroom species Agaricus bisporus (Lange) Imbach. The effect of formaldehyde treatment before using this compost is also considered. Materials were applied at different doses at spawning. Along with non-supplemented compost, three commercial nutritional supplements were used as controls.RESULTS: In general terms, grapeseed meal performance was similar to that of commercial delayed-release nutrients, but improved the non-supplemented compost response. We highlight that grapeseed enhances performance as larger yields of harvested mushrooms were obtained with greater dry weight content; however, their protein content was lower. The best performance was displayed by fresh formaldehyde-treated grapeseed (6000 ppm) when applied to the 10 g kg(-1) compost dose.CONCLUSIONS: Our findings suggest that grapeseed meal offers a great potential to be applied on a commercial scale. The addition of grapeseed resulted in an enhanced performance as shown by the higher number of harvested mushrooms. The use of grapeseed meal (extracted or non-extracted), a low-cost ingredient with high levels of carbohydrates, may suppose an economic profit on the basis of the positive effect of adding carbon in the mushroom cultivation. (C) 2012 Society of Chemical Industry
Keywords: mushroom; grapeseed; compost supplement; delayed-release nutrient; yield; quality